Aplikasi Pengolahan Data Panen TBS Kelapa Sawit pada PT. Jo Perdana Agri Technology - Lisnawanty; Muhammad Sony Maulana; Agung Sasongko; Miji (Jurnal Sistem Informasi, 2019)
Abstract— T. Jo Perdana Agry Technology is a company engaged in oil palm plantations that every day do processing data harvesting. Based on the results of observations that have been made, processing harvest data at PT. Jo Perdana Agry Technology has not been managed optimally where the data processing of crop processing is still done manually, causing the risk of losing data and inputting and searching data for a longer time. The purpose of this research is to discuss and design an application for harvesting data processing at PT. Jo Prime Agry Technology. This application is designed to be managed by two levels of users, namely Operations and Treasurers. Outputs produced in this data processing application include payment reports, harvest reports, shipping reports, general journals and ledgers. With this application, it is expected to facilitate the Operations and Treasurer in processing data on harvests and payments to contractors, as well as presenting outputs quickly and accurately.